Convergence of plasmid-mediated Colistin and Tigecycline resistance in Klebsiella pneumoniae - Zhao, Yujie; Qian, Changrui; Ye, Jianzhong; Li, Qingcao; Zhao, Rongqing; Qin, Ling; Mao, Qifeng (Frontiers in Microbiology, 2024)
Objective The co-occurrence of colistin and tigecycline resistance genes in Klebsiella pneumoniae poses a serious public health problem. This study aimed to characterize a K. pneumoniae strain, K82, co-harboring a colistin resistance gene (CoRG) and tigecycline resistance gene (TRG), and, importantly, investigate the genetic characteristics of the plasmid with CoRG or TRG in GenBank. Methods K. pneumoniae strain K82 was subjected to antimicrobial susceptibility testing, conjugation assay, and whole-genome sequencing (WGS). In addition, comparative genomic analysis of CoRG or TRG-harboring plasmids from K82 and GenBank was conducted. K. pneumoniae strain K82 was resistant to all the tested antimicrobials including colistin and tigecycline, except for carbapenems. Results WGS and bioinformatic analysis showed that K82 belonged to the ST656 sequence type and carried multiple drug resistance genes, including mcr-1 and tmexCD1-toprJ1, which located on IncFIA/IncHI2/IncHI2A/IncN/IncR-type plasmid pK82-mcr-1 and IncFIB/IncFII-type plasmid pK82-tmexCD-toprJ, respectively. The pK82-mcr-1 plasmid was capable of conjugation. Analysis of the CoRG/TRG-harboring plasmid showed that mcr-8 and tmexCD1-toprJ1 were the most common CoRG and TRG of Klebsiella spp., respectively. These TRG/CoRG-harboring plasmids could be divided into two categories based on mash distance. Moreover, we found an IncFIB/IncHI1B-type plasmid, pSYCC1_tmex_287k, co-harboring mcr-1 and tmexCD1-toprJ1. To the best of our knowledge, this is the first report on the co-occurrence of mcr-1 and tmexCD1-toprJ1 on a single plasmid. Conclusion Our research expands the known diversity of CoRG and TRG-harboring plasmids in K. pneumoniae. Effective surveillance should be implemented to assess the prevalence of co-harboring CoRG and TRG in a single K. pneumoniae isolate or even a single plasmid.